If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(y+1)=6y-34
We move all terms to the left:
2(y+1)-(6y-34)=0
We multiply parentheses
2y-(6y-34)+2=0
We get rid of parentheses
2y-6y+34+2=0
We add all the numbers together, and all the variables
-4y+36=0
We move all terms containing y to the left, all other terms to the right
-4y=-36
y=-36/-4
y=+9
| -x3=343 | | 16a=180 | | 6.x2-4x+27=0 | | 17-20z=-13-18z | | 3(2x-3)=4x-1 | | x+30=510+30=5 | | -2n-10=-5n+2+6n | | -5+10+9x+1=180 | | -5+10=9x+1 | | X^2-6x-62=-10 | | 2x+48+x-8+x=180 | | x+30=510+30=540 | | 8x+7x-66=44-7x | | -2m+7-5=20 | | 63=b-1.5 | | 32x-3=4x-1 | | 5(i-4)+6=8(i+7)-2(3i+5) | | x+2~7=4 | | -4-2(6x-2)^2=-86 | | 2i+5=2(i-7) | | 2x+43/10=0 | | 2x+328-3x)=3 | | 0=35x-4.9x^2 | | 125x=12.8 | | 4x-1+5x=2x-1 | | -4z-9=-7z | | 3i-4=5i-6-2i+2 | | .20x=80 | | -3j=-2j+12 | | 4b+15b=180 | | 11x+16=65 | | 6x2-10x-4=0 |